A phenomenological investigation of a female leader's perceptions and experience of discrimination in the work place - Mabovula, Nonceba (Rhodes University, Faculty of Education, Department of Education, 2003)
Women are now making their mark in virtually every economic sector including traditionally male strongholds of engineering, heavy transport, construction and manufacturing. Probably the most spectacular progress by women has been in the public sector. Many women now have voting rights, follow careers which demand that they work outside of the home, enjoy professional status equal to their male compatriots, occupy top leadership positions in their societies and, furthermore, fulfil their traditional roles of wife and mother. The present study is an attempt to explore a female eader's perceptions and experience of discrimination in her place of work. The problem has been that although there have been significant changes in women's increased representation in recent years, it is believed that women who succeed in obtaining top management posts still have to deal with unfair barriers. These need to be more carefully explored and understood. In this study I focus on one female leader's perceptions and experiences of leadership in an institution of higher learning. The advantages and disadvantages of such a small case study are discussed later. A phenomenological approach was used for obtaining information pertaining to the phenomenon "female leadership" , because phenomenology does offer ways of understanding not offered by other research methodologies. It enables the researcher to enter the lived world of the researched, and understand events and perceptions from a fresh point of view. A semi-structured interview was used to allow the respondent freedom to elaborate on responses in whatever manner she wished. The results obtained indicate that women are in a life-world in which, apart from the general experiences shared with their male counterparts, they are also exposed to many other forms of discrimination. Some of these are subtle, and result from years of socialisation into perceived gender role expectations. I hope that what I have discovered may help to contribute to the small but growing body of literature that seeks to understand women leaders' experiences, and perhaps in time play a role in enhancing their relative position in education and society at large.
Keywords: Sex discrimination against women; Sex discrimination in employment; Women -- Employment; Sexual division of labor; Women -- Economic conditions; Sex role in the work environment; Leadership in women